Advocacy in community-based service learning: perspectives of community partner organizations - Truong, Judy; Sandhu, Priya; Sadeghi , Yasamin; Sheng, Vanessa; Leung, Fok-Han; Wright, Roxanne; Suleman, Shazeen (Canadian Medical Education Journal, 2023)
Background: Health advocacy is a core competency for physicians, which can be developed through community-based service-learning (CBSL). This exploratory study investigated the experiences of community partner organizations (CPOs) participating in CBSL in the context of health advocacy. Methods: A qualitative study was conducted. Nine CPOs at a medical school participated in interviews on topics pertaining to CBSL and health advocacy. Interviews were recorded, transcribed, and coded. Major themes were identified. Results: CPOs perceived a positive impact from CBSL through student activities and connecting with the medical community. There was no unifying definition of health advocacy. Advocacy activities varied depending on the individual’s role (i.e., CPO, physician, and student), which encompassed providing patient care or services, raising awareness of healthcare issues, and influencing policy changes. CPOs had different perceptions of their role in CBSL from facilitating service-learning opportunities to teaching students in CBSL, while a few desired to be involved in curriculum development. Conclusion: This study provides further insight into health advocacy from the lens of CPOs, which may inform changes to health advocacy training and the CanMEDS Health Advocate Role to better align with the values of community organizations. Engaging CPOs in the broader medical education system may improve health advocacy training and ensure a positive bidirectional impact.